Xenopus M phase MAP kinase: isolation of its cDNA and activation by MPF. - Gotoh, Y (1991)
MAP kinase is activated and phosphorylated during M phase of the Xenopus oocyte cell cycle, and induces the interphase-M phase transition of microtubule dynamics in vitro. We have carried out molecular cloning of Xenopus M phase MAP kinase and report its entire amino acid sequence. There is no marked change in the MAP kinase mRNA level during the cell cycle. Moreover, studies with an anti-MAP kinase antiserum indicate that MAP kinase activity may be regulated posttranslationally, most likely by phosphorylation. We show that MAP kinase can be activated by microinjection of MPF into immature oocytes or by adding MPF to cell-free extracts of interphase eggs. These results suggest that MAP kinase functions as an intermediate between MPF and the interphase-M phase transition of microtubule organization.